FREE RADICAL AND ANTIOXIDANT PROPERTIES OF ALPINIA GALANGA (L.) WILLD - ARCHANA DAS; KUMARAN SIVANANDAN SANTHY (International Journal of Pharma and Bio Sciences, 2015)
Natural antioxidants presented in food and other biological materials have attracted considerable interest in the last few decades. In the present study, the antioxidant activity of Methanol Extract of Alpinia galanga (MEAG) was determined by using three complementary in vitro assays: Inhibition of DPPH and H2O2 radical & reducing power assay. The enzymic and non enzymic antioxidants were determined in the methanol extract of the rhizome by suitable colorimetric procedures. The results indicated a strong antioxidant potential of the plant extract. The effective concentration (EC50) sufficient to elicit 50% of a maximum effect was calculated to be 64 and 66 μg/ml for the DPPH and H2O2 radical scavenging respectively. The multiple antioxidant activity of MEAG was evident as it showed significant reducing power. The activity of Catalase in the rhizome was found to be maximum when compared to other enzymes assessed. The level of non-enzymic antioxidants (Ascorbic acid, α-tocopherol and polyphenols) were found in considerable amounts. From the results, it could be inferred that Alpinia galanga possesses innate antioxidant properties and therefore can be utilised for supplementing the antioxidant needs in the diet and for the treatment of various disorders caused due to oxidative damage.